2005
DOI: 10.1136/jnnp.2004.047993
|View full text |Cite
|
Sign up to set email alerts
|

Progression of structural neuropathology in preclinical Huntington's disease: a tensor based morphometry study

Abstract: Background and objectives: Regional cerebral atrophy occurs in carriers of the Huntington's disease (HD) gene mutation before clinical diagnosis is possible. The current inability to reliably measure progression of pathology in this preclinical phase impedes development of therapies to delay clinical onset. We hypothesised that longitudinal statistical imaging would detect progression of structural pathology in preclinical carriers of the HD gene mutation, in the absence of measurable clinical change. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
129
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(143 citation statements)
references
References 38 publications
12
129
1
1
Order By: Relevance
“…Due to its pivotal importance in these domains, changes in striatal physiology can contribute to multiple neurological diseases, including Huntington's disease, Parkinson's disease, dystonia, and others. An increasing number of reports suggest that changes in striatal synaptic physiology, including changes at glutamatergic, dopaminergic, and cholinergic synapses, are evident beginning in the prediagnostic phase of HD (5,6,(8)(9)(10)(11)(12)(13)(14)(35)(36)(37). These changes may contribute to early motor, cognitive, and psychiatric abnormalities, and could set the stage for the extensive pathophysiological alterations appearing later in the striatum.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its pivotal importance in these domains, changes in striatal physiology can contribute to multiple neurological diseases, including Huntington's disease, Parkinson's disease, dystonia, and others. An increasing number of reports suggest that changes in striatal synaptic physiology, including changes at glutamatergic, dopaminergic, and cholinergic synapses, are evident beginning in the prediagnostic phase of HD (5,6,(8)(9)(10)(11)(12)(13)(14)(35)(36)(37). These changes may contribute to early motor, cognitive, and psychiatric abnormalities, and could set the stage for the extensive pathophysiological alterations appearing later in the striatum.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented structural and functional brain changes in CAG-expanded individuals who have not yet been diagnosed (Aylward et al, 1996;Aylward et al, 2000;Aylward et al, 2004;Kipps et al, 2005;Paulsen et al, 2006b;Reading et al, 2004). Although relatively few studies have investigated the association between cognition and brain changes in HD, a recent study showed that cognitive task performance correlated with cerebral white matter and striatal volumes in early HD (Beglinger et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Both spatial pre-processing and statistical analysis were implemented in SPM2. Details regarding TBM image pre-processing are described in previous studies (Brambati et al, 2007;Kipps et al, 2005) (Fig. 1).…”
Section: Whole-brain Longitudinal Neuroimaging Analysis: Tensor-basedmentioning
confidence: 99%
“…In TBM volume changes are inferred from the non-linear deformation field required to warp two serial MRI scans. This technique has proven useful for tracking progression of atrophy in various neurodegenerative diseases (Chan et al, 2001a,b;Fox et al, 2000Fox et al, , 2001Fox et al, , 1999Fox and Freeborough, 1997;Freeborough et al, 1996;Kipps et al, 2005;Leow et al, 2006;Studholme et al, 2001). A TBM-like approach has been applied to serial scans of classic SD patients and has shown progression of atrophy in the temporal lobes (Cardenas and Studholme, 2004;Whitwell et al, 2004), but longitudinal neuroimaging studies of patients with predominant right or left temporal atrophy are still lacking.…”
Section: Introductionmentioning
confidence: 99%